'At the site of intimacy': An interview with Campbell X, January 2015. Issue 2 (1st March 2016) - Lewis, Reina
This article is an edited transcript of a conversation between Reina Lewis and film maker Campbell X recorded in London in 2015. The interview focuses on the racial, gender, and sexual politics of filmic representation and film production. A multi-award winning QTIPOC (queer trans intersex person of colour) filmmaker, based in London, Campbell's work has been instrumental in the development of queer British cinema. Centring on Campbell's 2012 feature film Stud Life, the article provides an historicised account of the development of Campbell's film practice, and examines the role of dress in the staging of LBGT characters and lives on screen. Providing insights into the process of costume design, casting, and film direction, Lewis and Campbell discuss the central role of dress, the body, and fashion in the visualisation of LGBT lives.